Endoscopic Observation of the Growth Process of a Right-Side Sessile Serrated Adenoma/Polyp with Cytological Dysplasia to an Invasive Submucosal Adenocarcinoma - Kaoru Omori; Kanako Yoshida; Sadafumi Tamiya; Tsutomu Daa; Masahiro Kan (Case Reports in Gastrointestinal Medicine)
A sessile serrated adenoma/polyp (SSA/P) with cytological dysplasia in the right colon, which transformed to an invasive submucosal adenocarcinoma finally, was endoscopically observed in a 76-year-old woman. A whitish soft SSA/P (approximately 25 mm in diameter) was detected in the cecum. Biopsy samples were obtained from the small nodule, and the lesion was eventually diagnosed as an SSA/P with cytological dysplasia, considering endoscopic observations, among which the narrow-band imaging features suggested that the lesion was adenomatous, that is, a round-oval pattern, and hyperplastic, that is, comprising a circular pattern with dots and an invisible capillary vessel. After 11 months, an SSA/P had rapidly developed into a submucosal adenocarcinoma with lymphatic infiltrations, and the most aggressive deep invasion was observed in the central depression. This case suggests that right-side SSA/Ps with cytological dysplasia should be removed immediately, considering the potential for rapid progression to a larger size and eventually to deep and extensive cancer.